Evaluation of integration of sustainable development in higher education in Sweden. Issue 4 (17th April 2020) - Finnveden, Göran; Friman, Eva; Mogren, Anna; Palmer, Henrietta; Sund, Per; Carstedt, Göran; Lundberg, Sofia; Robertsson, Barbro; Rodhe, Håkan; Svärd, Linn
Abstract : Purpose: Since 2006, higher education institutions (HEIs) in Sweden, should according to the Higher Education Act, promote sustainable development (SD). In 2016, the Swedish Government asked the Swedish higher education authority to evaluate how this study is proceeding. The authority chose to focus on education. This paper aims to produce a report on this evaluation. Design/methodology/approach: All 47 HEIs in Sweden were asked to write a self-evaluation report based on certain evaluation criteria. A panel was appointed consisting of academics and representatives for students and working life. The panel wrote an evaluation of each HEI, a report on general findings and recommendations, and gave an overall judgement of each HEI in two classes as follows: the HEI has well-developed processes for integration of SD in education or the HEI needs to develop their processes. Findings: Overall, a mixed picture developed. Most HEIs could give examples of programmes or courses where SD was integrated. However, less than half of the HEIs had overarching goals for integration of SD in education or had a systematic follow-up of these goals. Even fewer worked specifically with pedagogy and didactics, teaching and learning methods and environments, sustainability competences or other characters of education for SD. Overall, only 12 out of 47 got a higher judgement. Originality/value: This is a unique study in which all HEIs in a country are evaluated. This provides unique possibilities for identifying success factors and barriers. The importance of the leadership of the HEIs became clear.